Laboratory setup for synthetic aperture ultrasound imaging - TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2008)
The paper describes the synthetic transmit aperture (STA) imaging system with a single element transmitting and multi-element reception in medical ultrasound. Synthetic aperture method allows to achieve high electronic signal-to-noise ratio and good contrast resolution. A laboratory setup for acquisition of RF signals from linear transducer array was built. Simulated multichannel acquisition by multiplexing individual transducer was performed. In experiments 32-element linear transducer array with 0.48 mm inter-element spacing and a burst pulse with time duration 100 ns was used. Single element in the transducer transmitting aperture was used to generate a spherical wave covering the full image region. The echo signals were sampled independently by individual elements for each transmission. The comparison of 2D ultrasound images of wire phantom obtained using STA method and standard linear array scanning with commercial ultrasonograph is given. The results show excellent image resolution of the STA method and its robustness to refraction, attenuation and multiple reflection of ultrasound waves.